Point-like perturbation of Rashba Hamiltonian. Issue 1 (2nd January 2021) - Boitsev, A. A.; Brasche, J.; Popov, I. Y.
Abstract : Quantum system with spin–orbit interaction in three-dimensional space is considered. Point-like perturbation for Rashba Hamiltonian is constructed in the framework of the theory of self-adjoint extensions of symmetric operators. Boundary triplet approach is used. The Weyl function and the scattering matrix are constructed.